Bench to Any Side—The Pharmacology and Applications of Natural and Synthetic Alkylated Hydroxy Cinnamates and Cinnamides - José C. J. M. D. S. Menezes; Vinícius R. Campos (Compounds)
Natural alkylated hydroxy cinnamates (AHCs) isolated from medicinal plants and the thereby designed and synthesized cinnamides are derivatives of hydroxy cinnamic acids such as p-coumaric, sinapic, ferulic, and caffeic acids, which are naturally derived from human dietary sources. The pharmacological properties displayed by AHCs based on their inherent structure range include antioxidant, antimicrobial, antiplasmodial, anti-tyrosinase, Alzheimer’s and Parkinson’s disease therapy, anticancer therapy, metabolic disease therapy, and biopesticides, which have not been reviewed together. Based on their inherent antioxidant, antimicrobial, and UV absorption and their structure–activity relationships, these cinnamyl esters and amides can be used for food preservation in emulsions and oils, as sun-protective components of skin care formulations, and in many other multifunctional applications. In conclusion, the fine-tuning of the structural features such as the type of hydroxy cinnamic acid used, the length of alkyl chains for variable lipophilicity, conversion from cinnamic to propanoic for antioxidants, the increase in methoxy or the change to amino groups to increase the molar absorption coefficient and loss of absorption values, the substitution by halides or amino groups for potent biopesticides, and conversion from esters to amide bonds leads to different AHCs for biomedical, cosmetic, and agriculture applications as an emerging field of investigation that can overall provide natural, safe, biodegradable, and sustainable molecules.